Pengembangan layanan konseling online - Rika Fuaturosida; Ken Alfi Rozana; Yusuf Ratu Agung; Ali Ridho (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2022)
Abstract: This study aims to examine the development of an online counseling service website. The research method uses a quantitative survey. Subjects in this study amounted to 511 people. Where 317 subjects are UIN Malang and 194 subjects are outside UIN Malang. The initial activity in this research is to conduct counseling and then a google form will be given which contains a questionnaire on the satisfaction of using the website which also contains suggestions for the website. As for the results of filling out the questionnaire, subjects from outside UIN Malang are more open and assertive. The results of this study indicate that there is no difference in average between UIN Malang and outside UIN Malang with a significance value of 0.976 ( 0.05).Keywords: Service Development, Online Counseling, WebsiteAbstrak: Penelitian ini bertujuan untuk mengkaji pengembangan website layanan konseling online. Metode penelitian menggunakan kuantitatif survey. Subjek dalam penelitian ini berjumlah 511 orang. Dimana 317 subjek ialah UIN Malang dan 194 subjek ialah luar UIN Malang. Kegiatan awal dalam penelitian ini ialah dengan melakukan konseling lalu akan diberikan google form yang berisi angket kepuasan penggunaan website yang juga berisi saran terhadap website adapun hasil dari pengisian angket tersebut bahwasanya subjek dari luar UIN Malang lebih terbuka dan asertiv. Hasil penelitian ini menunjukan tidak terdapat perbedaan rata-rata antara UIN Malang dengan luar UIN Malang dengan nilai signifikansi 0,976 ( 0,05).Kata Kunci: Pengembangan Layanan, Konseling Online, Website